Evaluating the hydrological regime alteration under extreme climate scenarios in Southeast China - Zi-Mei Yang; Ying Chen; Xing-Wei Chen; Lu Gao; Hai-Jun Deng; Mei-Bing Liu (Journal of Hydrology: Regional Studies, 2024)
Study region: The Shanmei Reservoir Watershed (SRW), Southeast China. Study focus: This study investigated the climate and hydrological regimes alterations in a subtropical coastal watershed (SRW) during the 21st century in extreme scenarios. The extreme scenarios, i.e., warm-wet and cold-dry climates, were constructed using 18 global climate models (GCMs) from CMIP6 under shared socioeconomic pathways (SSP1–2.6, SSP2–4.5, SSP3–7.0 and SSP5–8.5). The Soil and Water Assessment Tool (SWAT) model and Indicators of Hydrologic Alteration (IHA) were applied to quantify the impacts of climate change on the eco-hydrological regimes during the projected period (2041–2100) compared to the base period (1980–2014). New hydrological insights for the region: The results show that the average temperature rises by 0.6–3.8 ℃, and the average annual precipitation changes by −21.4 % - 32.4 % by the end of the 21st century under extreme scenarios. Contrasting hydrological regimes are expected in the SRW under extreme scenarios. Under the extreme warm-wet scenarios, the monthly runoff is lower during spring and higher during summer, the minimum flows are significantly higher, and the maximum and minimum flows occurs earlier. Water resource utilization and ecosystem health are expected to improve. However, the opposite holds true in the cold-dry scenarios. The hydrologic regime alteration under future extreme climate scenarios can guide local water planning and ecological restoration strategies.